Beyond Size: How ESG Factors Shape Bank Value in India & China - Naidu, Dr. M. Purushottam; Lakshmi, Dr. V. Gowri; Kasturi, Dr. G. V. K.; Patnaik, Dr. R. Pradeep Kumar; M., Muniratnam; Ganesh V., Chaitanya; P., Harshavardhan (Migration Letters, 2024)
Objective: This study examines the impact of ESG (environmental, social, and governance) factors on the market capitalization of banks in India and China. Specifically, it analyses the relationship between total assets, female board representation, social and environmental disclosures, and market capitalization. Methods: A comparative analysis of leading banks in India and China is conducted using 10 year (2013–2023) data using structural equation modelling (SEM) on market capitalization, total assets, ESG disclosures, and female board representation. Results: A positive and significant relationship is found between total assets and market capitalization in both India and China, indicating that investors value larger banks. In India, female board representation doesn’t significantly impact market capitalization, while in China, a higher proportion may lead to lower market capitalization, requiring further research. A positive and significant relationship is found between social and environmental disclosures and market capitalization in both countries. However, the effect is stronger in India, indicating that Indian investors place greater value on banks with robust sustainability practices. Conclusions: This study highlights the growing importance of ESG factors in the banking sector, with varying degrees of emphasis depending on the country. While both Indian and Chinese investors value larger banks, Indian investors seem to place more weight on female board representation and social-environmental disclosures, while Chinese investors appear to prioritize other factors. Further research is needed to explore the underlying reasons for these differences and the complex interplay between various ESG factors and market performance.